2018
DOI: 10.1093/rheumatology/key369
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate achieves major cDAPSA response, and improvement in dactylitis and functional status in psoriatic arthritis

Abstract: Objective Despite the widespread clinical use of MTX in PsA, data from published randomized controlled studies suggest limited efficacy. The objective of the present study was to document the efficacy of MTX. Methods This was an open-label, prospective study of patients satisfying the ClASsification criteria for Psoriatic ARthritis study (CASPAR) criteria for PsA who received MTX in doses of ⩾15 mg/week throughout the follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
3
5
0
1
Order By: Relevance
“…Both methotrexate and apremilast resulted in significant improvement in skin involvement in our study and there was no difference in change in PASI score between the two groups at 24 weeks. Similar results were noted in previous studies on the use of methotrexate and apremilast in patients with PsA [7,10,11,[13][14][15][16]18].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Both methotrexate and apremilast resulted in significant improvement in skin involvement in our study and there was no difference in change in PASI score between the two groups at 24 weeks. Similar results were noted in previous studies on the use of methotrexate and apremilast in patients with PsA [7,10,11,[13][14][15][16]18].…”
Section: Discussionsupporting
confidence: 91%
“…Major cDAPSA response at 24 weeks was noted in 20% patients in the apremilast group and 37.5% in the methotrexate group in our study. Previously, Appani et al reported major cDAPSA response in 43.8% of patients receiving methotrexate for 24 weeks, which is similar to that noted in our study [7]. Although there is no data about the major cDAPSA response with apremilast, recently Mease et al in their post-hoc analysis showed that around 25-47% patients achieved cDAPSA remission/low disease activity with apremilast depending on baseline disease activity [8].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…[28] In yet another open label trial assessing the efficacy of methotrexate in various domains of PsA, a significant drop in mean LEI scores from 1.6 to 0.1 were noted in 6 months. [29] Assessment of efficacy of methotrexate in the TICOPA trial demonstrated a significant change in the proportion of patients with enthesitis from baseline to 12 weeks. [30] In this context, findings of the current study will have important implications for clinical practice in resource constrained settings that are heavily dependent on cDMARDs.…”
Section: Discussionmentioning
confidence: 99%
“…O papel benéfico do metotrexato (MTX) sobre o domínio cutâneo, artrite periférica, dactilite e a maior probabilidade de alcançar a mínima atividade de doença tem sido demonstrado desde os primeiros dados dos estudos TICOPA (Tight Control of PsA) e MIPA (Methotrexate in Psoriatic Arthritis study). Por outro lado, os resultados sobre a entesite propriamente dita não são robustos [16][17][18][19] e, provavelmente, não demonstraram eficácia com relação a esse domínio até o momento. Além disso, não tem sido demonstrado qualquer efeito adicional na combinação com os inibidores do TNF-α 20 .…”
Section: Figura 1 Entesopatias -Abordagem Global E Tomada De Decisãounclassified